The Effect of Fly Ash Substitution in 3 Brands of PCC Cement on The Compressive Strength f Concrete - Aliansyah, Zulfikar Jati; Firdaus, Firdaus (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Fly ash, a by-product of coal combustion in thermal power plants is utilized as a substitute for Portland Cement in concrete due to its pozzolanic properties. Mainly, class F fly ash—produced from the combustion of anthracite coal at approximately 1560˚C (according to SK SNI S15-1990-F)—contains less than 10% lime (CaO) and exhibits significant pozzolanic or filler properties. This research investigates the impact of varying fly ash proportions (0%, 10%, 15%, and 20%) on the compressive strength of concrete. The experimental setup included 108 cylindrical test specimens (10 cm in diameter and 20 cm in height), representing different brands of cement and fly ash mixtures, tested at 7, 14, and 28 days. The study was conducted at PT. Waskita Beton Precast Plant in Sadang, Purwakarta, West Java, targeting a concrete compressive strength of 40 MPa. Results indicate that at 0% fly ash, the compressive strength using Garuda Cement reached 76.66 MPa after 28 days. However, this strength decreased with increasing fly ash content, measuring 72.35 MPa, 69.07 MPa, and 68.13 MPa for 10%, 15%, and 20% fly ash, respectively. These findings highlight the influence of fly ash content on the structural integrity of concrete, suggesting a potential trade-off between sustainability and mechanical performance. Keyword: Fly Ash, Compressive Strength of Concrete, Portland Cement